Frameless single-isocenter intensity modulated stereotactic radiosurgery for simultaneous treatment of multiple intracranial metastases - Lau, Steven K. M. (Transl Cancer Res, 2014)
PURPOSE: Stereotactic radiosurgery (SRS) is well accepted treatment for patients with intracranial metastases, but the role of frameless radiosurgery is not well defined. Here, we describe our clinical experience applying a novel single-isocenter technique to frameless intensity modulated stereotactic radiosurgery (IMRS) for simultaneous treatment of multiple intracranial metastases. METHODS AND MATERIALS: Between 2006 and 2012, 100 consecutive patients received frameless IMRS for multiple intracranial metastases using a single, centrally-located isocenter. Among these, 29 patients were treated for progressive or recurrent intracranial disease. A total of 465 metastases (median, 4 per patient, range, 2–18) were treated to a median dose of 20 Gy (range, 15–50 Gy). Follow-up including clinical examination and magnetic resonance imaging (MRI) occurred every 3 months. RESULTS: Median follow-up for all patients was 4.3 months (range, 0.2–58.3 months), with 83 patients (83.0%) followed until their death. For the remaining 17 patients alive at the time of analysis, median follow-up was 9.2 months (range, 2.2–58.3 months). Overall survival at 6 months was 49.5% [95% confidence interval (CI), 35.3–63.6%]. Local control at 6 and 12 months was 88.9% (95% CI, 79.1–98.6%) and 81.5% (95% CI, 65.2–97.7%), respectively. Regional failure was observed in 39 patients (39%), and 25 patients (25%) received salvage therapy. Grade 3 or greater treatment-related toxicity was observed in 4 patients (4%) and included intracranial hemorrhage, seizure, and radionecrosis. Median total treatment time was 17.2 minutes (range, 2.8–55.3 minutes). CONCLUSIONS: Single-isocenter IMRS for multiple intracranial metastases can produce clinical outcomes comparable to those of conventional radiosurgery techniques.